2016
DOI: 10.1016/j.pnpbp.2015.02.013
|View full text |Cite
|
Sign up to set email alerts
|

The neuroprotective potential of low-dose methamphetamine in preclinical models of stroke and traumatic brain injury

Abstract: Methamphetamine is a psychostimulant that was initially synthesized in 1920. Since then it has been used to treat attention deficit hyperactive disorder (ADHD), obesity and narcolepsy. However, methamphetamine has also become a major drug of abuse worldwide. Under conditions of abuse, which involve the administration of high repetitive doses, methamphetamine can produce considerable neurotoxic effects. However, recent evidence from our laboratory indicates that low doses of methamphetamine can produce robust n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 47 publications
(78 reference statements)
0
19
0
Order By: Relevance
“…This hypothesis is consistent with the understanding that dopamine is anti-inflammatory by inhibiting the activation of NOD-like receptor containing Pyrin domain-3 (NLRP3) inflammasome by D1R activation ( Yan et al, 2015 ). Additional studies have shown that low doses of MA, which increase dopamine release, are neuroprotective following oxygen-glucose deprivation ( Rau et al, 2016 ). However, it remains to be determined how abstinence from MA contributes to increases in PGJ2.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is consistent with the understanding that dopamine is anti-inflammatory by inhibiting the activation of NOD-like receptor containing Pyrin domain-3 (NLRP3) inflammasome by D1R activation ( Yan et al, 2015 ). Additional studies have shown that low doses of MA, which increase dopamine release, are neuroprotective following oxygen-glucose deprivation ( Rau et al, 2016 ). However, it remains to be determined how abstinence from MA contributes to increases in PGJ2.…”
Section: Discussionmentioning
confidence: 99%
“…The above findings may suggest that the neuroprotective and/or neurorestorative properties of METH observed in preclinical models are dosage and time-dependent [192], and may exert a similar role in humans. It is hypothesized that the activation of the dopaminergic Compared to saline, METH treatment significantly improved recovery of behavioral functions (reduction of modified neurological severity scores and foot-fault score errors up to 6 weeks after TBI).…”
Section: Model Of Methamphetamine Administration Main Resultsmentioning
confidence: 83%
“…However, the results of the present study suggest that an individual who has taken amphetamines may function at a better motor level after head trauma than one who has not been exposed, possibly due to the dopaminergic effects of the drug. Whether this is due to a direct neuroprotective effect, as has been suggested in other animal studies , or merely an enhanced “flight or fight” response from increased arousal is unclear, although it would appear unlikely that the enhanced performance would be due to a “flight or fight” response after a delay of 7 days. It is also possible that both elements may come into play, either sequentially or synergistically, resulting in an individual with an otherwise incapacitating head injury being able to leave the area of an attack, to defend him or herself more effectively than without the drug, or to continue with a physical attack against another.…”
Section: Discussionmentioning
confidence: 87%
“…There are, however, studies that have demonstrated low‐dose methamphetamine administered soon after severe TBI in a rodent model may have a neuroprotective effect. It is hypothesized that amphetamines, by blocking the reuptake and increasing the release of dopamine, protect the brain from the effects of excitotoxicity resulting in reduced neuronal loss and apoptotic cell death, with less neuromotor/cognitive impairment . Methamphetamine has also been shown to reduce pericontusional perfusion after TBI and has been shown on imaging to improve white matter reorganization after injury .…”
Section: Discussionmentioning
confidence: 99%